«The ghosts of history: a deconstructive approximation to the past» (2020)
The focus of this chapter draws from my book Haunting History to articulate a deconstructive approach to the past as something that haunts the present, like a ghost. In so doing, I address the current state of the theory of history and the persistence of ontological realism as the dominant mode of thought for conventional historians. I instead advocate a hauntological approach to history that follows the work of Jacques Derrida and embraces a past that is at once present and absent, available and restricted, polysemic and multiple, rather than a fixed and static snapshot of a moment in time.